Longterm outcome of photodynamic therapy compared with biliary stenting alone in patients with advanced hilar cholangiocarcinoma - Cheon, Young Koog (Blackwell Publishing Ltd, 2012)
OBJECTIVES: This study aimed to determine longterm outcomes and factors associated with increased survival after photodynamic therapy (PDT) compared with endoscopic biliary drainage alone in patients presenting with advanced hilar cholangiocarcinoma (CC). METHODS: A retrospective analysis of the institutional database identifying all patients who presented with a diagnosis of hilar CC between December 1999 and January 2011 was conducted. RESULTS: Of the 232 patients identified, 72 (31%) were treated with PDT (Group A) and 71 (31%) were treated with endoscopic biliary drainage alone (Group B). Median survival was 9.8 months [95% confidence interval (CI) 7.42–12.25] in Group A and 7.3 months (95% CI 4.79–9.88) in Group B (P= 0.029). On multivariate analysis, biliary drainage without PDT (P= 0.025) and higher T-stage (P= 0.002) were significant predictors of shorter survival in all patients. In a subgroup analysis of patients in the PDT group, lower pre-PDT bilirubin level (P= 0.005), multiple PDT treatments (P= 0.044) and shortened time to treatment after diagnosis (P= 0.013) were significant predictors of improved survival. Median metal stent patency was longer in Group A than in Group B (215 days vs. 181 days; P= 0.018). CONCLUSIONS: Photodynamic therapy with stenting resulted in longer survival than stenting alone. Early PDT after diagnosis and multiple PDT treatments were shown to have survival benefits. Metal stent patency was longer in patients receiving PDT. Higher T-stage appears to be a predictor of early mortality in advanced bile duct cancer treated with PDT.